Revisiting Class-Based Affirmative Action in Government Contracting - Jarrod D. Reece (Washington University Law Review, 2011)
The Article highlights the existing class-based alternatives to affirmative action in government contracting based on races in the U.S. in 2011. It discusses the theory of class-based affirmative action, state-by-state anti-affirmative action movement and the history of affirmative action. It explores three programs aimed to encourage the development of job in disadvantaged areas by government contracting and show the ways on how each program is structured.
Keywords: Affirmative action; Government contracts; United States